18F-FBPA PET in Sarcoidosis: Comparison to Inflammation-Related Uptake on FDG PET. (November 2020) - Watabe, Tadashi; Shimamoto, Hiroaki; Naka, Sadahiro; Kamiya, Takashi; Murakami, Shumei
Abstract : Abstract: A 68-year-old man with sarcoidosis showed high 18 F-FDG uptake in the mediastinal and hilar lymph nodes on 18 F-FDG PET, suggesting active inflammation. 18 F-fluoro-boronophenylalanine (FBPA) PET showed no significant uptake in the mediastinal and hilar lymph nodes, suggesting its cancer specificity as a substrate of L-type amino acid transporter 1. 18 F-fluoro-boronophenylalanine PET can be used for precise evaluation in oncology when the differentiation between inflammation and metastasis is inconclusive on 18 F-FDG PET.